THE EFFECT OF PROFITABILITY, FINANCIAL LEVERAGE, COMPANY SIZE ON EARNINGS MANAGEMENT IN THE AUTOMOTIVE SUBSECTOR - Sofya Salwa Aurel; Yona Octiani Lestari (LPPM STIE Muhammadiah Bandung, 2025)
Listed on the Indonesia Stock Exchange (BEI) over the years 2021–2023, this study aims to analyze the impact of profitability, financial leverage, and company size on profits management in the automotive subsector. In this quantitative research, PT Astra International Tbk, PT Astra Otoparts Tbk, and PT Gajah Tunggal Tbk are among the ten automotive firms that were selected using a purposive sampling process. The data used for this study came from yearly financial reports and was analyzed using SPSS software for multiple linear regression. Based on the data, it seems that firms with greater levels of debt are less likely to manipulate their profits. This might be because creditors are more vigilant in their surveillance of companies with high levels of debt. Contrarily, earnings management is unaffected by business size or profitability, which may indicate that enterprises are focusing on recovering from the epidemic rather than manipulating their financial statements. These results provide important insights for regulators and investors in comprehending the elements impacting the reliability of financial reporting, in addition to making theoretical contributions to the field of accounting. Financial reporting should be more open and honest, according to the study, and future research should look at other aspects including audit quality.